A middle Permian ophiolite fragment in Late Triassic greenschist- to blueschist-facies rocks in NW Turkey: An earlier pulse of suprasubduction-zone ophiolite formation in the Tethyan belt - Topuz, Gültekin; Schwarz, Winfried H.; Altherr, Rainer (Lithos, 2018)
The Eastern Mediterranean region within the Tethyan belt is characterised by two main pulses of suprasubduction-zone ophiolite formation during the Early-Middle Jurassic and Late Cretaceous. Despite vast exposures of the Permo-Triassic accretionary complexes, related suprasubduction-zone ophiolites and the timing of subduction initiation leading to the formation of Permo-Triassic accretionary complexes are unknown so far. Here we report on a ~40km long and 0.3 to 1.8km wide metaophiolite fragment within transitional greenschist- to blueschist-facies oceanic rocks from NW Turkey. The metaophiolite fragment is made up mainly of serpentinite and minor dykes or stocks of strongly sheared metagabbro with mineral assemblages involving actinolite/winchite, chlorite, epidote, albite, titanite and phengite. The metagabbro displays (i) variable CaO and MgO contents, (ii) anomalously high Mg# (=100∗molar MgO/(MgO+FeOtot)) of 75-88, and (iii) positive Eu anomalies, together with low contents of incompatible elements such as Ti, P and Zr, suggesting derivation from former plagioclase cumulates. The serpentinites comprise serpentine, ±chlorite, ±talc, ±calcite and relict Cr-Al spinel surrounded by ferrichromite to magnetite. Relict Cr-Al spinels are characterised by (i) Cr/(Cr+Al) ratios of 0.45-0.56 and Mg/(Mg+Fe2+) ratio of 0.76-0.22, (ii) variable contents of ZnO and MnO, and (iii) extremely low TiO2 contents. Zn and Mn contents are probably introduced into Cr-Al spinels during greenschist- to blueschist metamorphism. Compositional features of the serpentinite such as (i) Ca- and Al-depleted bulk compositions, (ii) concave U-shaped, chondrite-normalised rare earth element patterns (REE) with enrichment of light and heavy REEs, imply that serpentinites were probably derived from depleted peridotites which were refertilised by light rare earth element enriched melts in a suprasubduction-zone mantle wedge. U-Pb dating on igneous zircons from three metagabbro samples indicates igneous crystallisation at 262Ma (middle Permian). Timing of the metamorphism is constrained by incremental 40Ar/39Ar dating on phengitic white mica at 201Ma (latest Triassic). We conclude that the metaophiolite represents a fragment of middle Permian suprasubduction-zone oceanic lithosphere, involved in a latest Triassic subduction zone. These data, together with several reports in literature, indicate that the middle Permian was a time of suprasubduction-zone ophiolite formation in the Tethyan belt.